A comparative study of the association between childhood trauma and depression disorder among first-year MBBS and physiotherapy students - Shraddha Jadhav; Bhoomi Jodhani; Rajesh Dase (MGM Journal of Medical Sciences, 2025)
Background: Depressive disorders are a major public health concern and are often linked to childhood trauma (CT), which includes various forms of abuse and neglect. CT can interfere with emotional and psychological development, increasing susceptibility to depression and anxiety later in life. Early exposure to trauma affects brain development and stress regulation systems, contributing to chronic stress and mood disorders. Materials and Methods: This cross-sectional study was conducted at MGM Medical College and Hospital, Chhatrapati Sambhajinagar (Aurangabad), Maharashtra, India, and included 176 first-year MBBS and physiotherapy students, with 88 participants from each group. Data on participants’ backgrounds and health information were collected using a structured form. The Childhood Trauma Questionnaire-Short Form (CTQ-SF) was employed to assess childhood abuse experiences, while the Hamilton Depression Rating Scale (HAM-D) was used to evaluate depression levels. Results: Among the 176 students, CTQ-SF results indicated that 91 reported no history of trauma, whereas 85 had experienced some form of CT. Of those with a history of trauma, 28 students (P = 0.68) exhibited depressive symptoms according to the HAM-D scale, suggesting a potential association between CT and depression. Conclusion: The study highlights a significant prevalence of CT among students, with a possible link to depressive symptoms. These findings emphasize the need to address CT to promote mental well-being in young adults. Educational institutions should implement support programs and workshops on trauma awareness and coping strategies. Creating safe spaces for students to share their experiences and ensuring access to counseling services can help mitigate the effects of trauma and foster better mental health outcomes.